Hubungan Antara Analisis Time-Motion Terhadap Hasil Pertandingan Judo Pada Pekan Olahraga NasionaL (PON) XX Tahun 2021 - Salsa Santika; Kardjono Kardjono; Pipit Pitriani; Ira Purnamasari (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to determine the relationship between time- motion analysis on the results of the Judo match at the XX National Sports Week (PON) in 2021. The research method used was a descriptive correlational research method. The population used in this study was a video match of West Java Judo athletes who competed at the XX National Sports Week (PON) 2021 in Papua, totaling 15 athletes. The author uses a convenience sampling technique, the author only analyzes West Java athletes who compete in the fighting or sparring category. The research instrument used is videos of Judo matches at the XX National Sports Week (PON) in 2021 in Papua which will be analyzed in time-motion using a stopwatch. Data collection techniques were carried out by analyzing judo match videos. The data processing technique uses three methods, namely descriptive statistics, normality tests, and correlation tests. The results of the study indicate that time-motion analysis does not have a significant effect on the results of judo matches. So it can be concluded that the relationship between these variables has no relationship or is not correlated.